Silencing hsa_circ_PVT1 (circPVT1) suppresses the growth and metastasis of glioblastoma multiforme cells by up-regulation of miR-199a-5p. Issue 1 (1st January 2020) - Chi, Guonan; Yang, Fuwei; Xu, Donghui; Liu, Weiming
Abstract: Background: Glioblastoma multiforme (GBM) is one of the most prevailing primary brain tumours among adults and most aggressive cancers. Despite multiple developments in medical and surgical treatments, GBM is still a deadly disease with a high mortality rate. Here, this study was performed to investigate the function of circPVT1 on GBM. Methods: CCK-8 and flow cytometry were utilised to estimate viability and apoptosis in both cells. qRT-PCR was performed to determine circPVT1 and miR-199a-5p expression. Western blot was conducted to determine apoptosis, migration and EMT-related proteins levels when silencing circPVT1. Subsequently, these parameters were re-tested after up-regulating miR-199a-5p. Results: CircPVT1 was highly expressed in GBM tissues. Silencing circPVT1 raised two cells apoptosis and reduced viability and migration capacity. Moreover, EGF-induced EMT was repressed by silencing circPVT1. In addition, miR-199a-5p expression was elevated when silencing circPVT1. And silencing circPVT1 exerted above changes via up-regulating miR-199a-5p. Finally, silencing circPVT1 repressed YAP1 and PI3K/AKT pathways via up-regulating miR-199a-5p. Conclusion: Our data suggested that silencing circPVT1 inhibited viability, migration, EGF-induced EMT and promoted apoptosis as well as repressed YAP1 and PI3K/AKT pathways by up-regulating miR-199a-5p. HIGHLIGHTS: CircPVT1 expression is highly expressed in GBM tissues; Si-circPVT1 represses migration and promoted apoptosis in U539 and U251 cells; Si-circPVT1 represses migration and promoted apoptosis when elevating miR-199a-5p; Si-circPVT1 represses EGF-induced EMT when increasing miR-199a-5p; Si-circPVT1 suppresses YAP1 and PI3K/AKT pathways by up-regulating miR-199-5p.